Eficácia antimicrobiana de preparações alcoólicas comercializadas no Brasil para higienização das mãos de profissionais da saúde - Guilhermetti, Marcio (2009)
In recent years, several commercial alcohol-based hand gels have appeared on the market to improve the hand-cleansing compliance of health-care workers. Although the antimicrobial efficacy of these products has been reported in different countries, in Brazil few studies have investigated this subject. In this study, we assessed the antimicrobial efficacy of 12 alcoholbased hand gels produced in Brazil, containing 70% w/w or v/v ethyl alcohol as the active ingredient, according to the European Standard EN 1500 (EN-1500). In addition, 70% w/w ethyl alcohol and three alcohol-based hand rubs, commonly used in Europe and effective according to EN-1500, were also tested. All the products tested, except for two alcohol gels produced in Brazil, were approved by the EN-1500 test protocol with a 60-second application. The results confirmed the antimicrobial efficacy of the majority of the alcohol gels produced in Brazil for hand hygiene of health-care workers.